Determination of clinically acceptable cut-offs for hemolysis index: An application of bootstrap method using real-world data - Cao, Yang; Branzell, Ida; Vink, Martin (Clinical biochemistry, 2021)
To assess the impact of hemolysis on laboratory results under local conditions and to verify the hemolysis index cut-off for potassium using real-world data. The statistical bootstrapping method was performed on 54,125 samples collected at the University Hospital of Örebro (USÖ). The results were compared to a method based on stratification of samples according to hemolysis level, and on paired difference testing. Setting the acceptable allowable limit of error to 10%, the three assessed strategies yielded comparable results with respect to the impact of haemolytic interference on test results for potassium. The suggested cut-offs were 111 mg Hb/dL for the bootstrapping method, between 125–150 mg Hb/dL for the method based on stratification, and around 150 mg/dL for the paired difference testing strategy. The impact of hemolysis on potassium measurement is likely different between primary care patients and inpatients. Using the effect of hemolysis on potassium measurement as a model, a novel approach towards finding clinically acceptable limits for analytical interference is presented, that relies on the bootstrapping method and on actual patient data from routine laboratory operation, hence incorporating local population characteristics, equipment and instrumental settings.